The investigation of middle school mathematics textbooks in terms of mathematics’ connection to nature and science - Durmus, Soner; Kirenli, Serdar (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2024)
Effective education depends on various factors, with textbooks and courses being essential for preparing students for real life situations. Therefore, it's crucial that textbooks are thoughtfully developed and chosen. This study investigates how middle school mathematics textbooks approved by the Ministry of National Education for the 2021-2022 academic year address the connections between “Mathematics - Science” and “Mathematics - Nature.” As a descriptive research study, it seeks to reveal the current state of these connections. Data was collected through document analysis, a qualitative research method. Within the scope of this study, eight middle school mathematics textbooks were examined, two from each grade level. The analysis was organized according to the curriculum, emphasizing science and nature themes, as identified through curriculum goals and educational literature. These themes were identified by examining the mathematics curriculum goals and literature on effective mathematics education and textbooks. The research found that while content associations with science and social sciences were somewhat adequate, they were lacking in nature and art. Additionally, connections to daily life were well-represented and designed to engage students. It is recommended that future efforts should aim to enhance textbook preparation to better align with contemporary educational needs.